Autobiographical Thinking Interferes with Episodic Memory Consolidation - Craig, Michael; Della Sala, Sergio; Dewar, Michaela (PLOS ONE, 2014)
New episodic memories are retained better if learning is followed by a few minutes of wakeful rest than by the encoding of novel external information. Novel encoding is said to interfere with the consolidation of recently acquired episodic memories. Here we report four experiments in which we examined whether autobiographical thinking, i.e. an ‘internal’ memory activity, also interferes with episodic memory consolidation. Participants were presented with three wordlists consisting of common nouns; one list was followed by wakeful rest, one by novel picture encoding and one by autobiographical retrieval/future imagination, cued by concrete sounds. Both novel encoding and autobiographical retrieval/future imagination lowered wordlist retention significantly. Follow-up experiments demonstrated that the interference by our cued autobiographical retrieval/future imagination delay condition could not be accounted for by the sound cues alone or by executive retrieval processes. Moreover, our results demonstrated evidence of a temporal gradient of interference across experiments. Thus, we propose that rich autobiographical retrieval/future imagination hampers the consolidation of recently acquired episodic memories and that such interference is particularly likely in the presence of external concrete cues.